Blastocyst rate of in vitro embryo production in sheep is affected by season. Issue 3 (August 2014) - Mara, L.; Sanna, D.; Casu, S.; Dattena, M.; Muñoz, I.M. Mayorga
Summary It has been reported that the number and quality of in vitro produced embryos is season related. This study was conducted to assess the effect of season on cleavage, blastocyst and lambing rates of in vitro produced ovine embryos during 3 years of collection data. Ovaries of Sarda sheep were collected from a slaughterhouse. In total, 5035 oocytes were recovered and matured in TCM-199 with 4 mg/ml bovine serum albumin (BSA), 100 μM cysteamine, 0.3 mM Na pyruvate, 0.1 UI/ml recombinant follicle-stimulating hormone (r-FSH), 0.1 UI/ml recombinant luteinising hormone (r-LH), and 1 μg/ml estradiol-17β. Matured oocytes were fertilized with fresh semen in synthetic oviductal fluid (SOF) with 20% heat inactivated estrous sheep serum. The presumptive zygotes were cultured for 6–7 days (blastocyst stage) in SOF medium supplemented with 1% Basel Medium Eagle (BME), 1% Minimum Essential Medium, 1 mM glutamine and 8 mg/ml fatty acid-free BSA. The embryos produced were vitrified and a total of 165 blastocysts (80 from the breeding season and 85 from the anoestrous season) were transferred in pairs into recipient ewes during the reproductive period. There were no significant differences in cleavage rates between seasons in any of the 3 years examined (84% versus 83%, 81% versus 80% and 80% versus 79%, respectively). The blastocyst rate varied significantly between seasons in 2005 and 2007 (P < 0.05), and in 2006 (P < 0.001). There were no differences in pregnancy and lambing rates between embryos during anoestrous versus during the breeding season. In conclusion, only the blastocyst rate appeared to have been affected by season, possibly due to variation in the number of developmentally competent oocytes.